Evaluating the STRATMOD transport model: Case Trondheim - Skatvedt, Ola; Tørset, Trude (Proceedings from the Annual Transport Conference at Aalborg University, 2018)
The purpose of this paper is to discuss the usefulness of the transport model ’STRATMOD’, a simplified transport model. Transport models are often complex and have long run-times which STRATMOD improves by aggregating travel matrices from a baseline strategic transport model, and using elasticities to calculate the effects of measures. The model is tested with a sensitivity analysis on input- elasticities, and by analysing the metro-bus project in Trondheim. The model is useful, especially when analysing public transport measures with improvements in quality factors. It is however a bit inaccurate in practical use, because of insecurities with input- elasticities, and difficulties in deciding what effect the planned measures will have for the quality factors of the public transport system as a whole.